Payroll Accounting Information System Analysis on CV. Rindang Khatulistiwa Jember - Fatimatuzzahro, Salsabila; Yulinartati, Yulinartati; Ari Sita Nastiti (Westscience Press, 2024)
The purpose of this research is to find out an overview of the payroll accounting information system at CV. Shady Equatorial Jember. Starting from activities in the payroll system to reports generated from the payroll system. Data collection methods use observation, interviews and documentation. The data analysis technique used is a qualitative descriptive analysis technique, namely by describing the payroll accounting information system in the company including activities in the payroll system, documents used, related accounting records, reports produced and functions related to the system. payroll accounting information. Then it is analyzed whether the payroll accounting information system implemented in the company can increase effectiveness and efficiency in the payroll process. The research results show that the implementation of the payroll accounting information system at CV. Rindang Khatulistiwa Jember is still not effective, because in CV. Rindang Khatulistiwa Jember still uses a manual system.